2013
DOI: 10.1016/j.yexcr.2012.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for protein kinase A in the phosphorylation of the TGFβ receptor-interacting protein km23-1 as a component of TGFβ downstream effects

Abstract: km23-1 was previously identified as a TGFß-receptor interacting protein that was phosphorylated on serines after TGFß stimulation. In the current report, we examined the role of km23-1 phosphorylation in the downstream effects of TGFß/ protein kinase A (PKA) signaling. Using phosphorylation site prediction software, we found that km23-1 has two potential PKA consensus phosphorylation sites. In vitro kinase assays further demonstrated that PKA directly phosphorylates km23-1 on serine 73 (S73). Moreover, our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
7
1
Order By: Relevance
“…We have characterized a new conditional knockout model for the DYNLRB1 subunit of dynein and use this model to show that DYNLRB1 is required for retrograde axonal transport of a broad spectrum of cargos in sensory axons, as well as for neuronal survival. These findings were surprising given the notion that DYNRLB1 should function mainly as a binding adaptor for TGFβ signaling complexes and other specific cargos [11,[14][15][16][17][18], whereas our data suggests that DYNLRB1 is essential for dynein-mediated axonal transport of lysosomes, late endosomes and signaling endosomes.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…We have characterized a new conditional knockout model for the DYNLRB1 subunit of dynein and use this model to show that DYNLRB1 is required for retrograde axonal transport of a broad spectrum of cargos in sensory axons, as well as for neuronal survival. These findings were surprising given the notion that DYNRLB1 should function mainly as a binding adaptor for TGFβ signaling complexes and other specific cargos [11,[14][15][16][17][18], whereas our data suggests that DYNLRB1 is essential for dynein-mediated axonal transport of lysosomes, late endosomes and signaling endosomes.…”
Section: Discussioncontrasting
confidence: 87%
“…DYNLRB protein sequence is highly conserved among different species; with two isoforms, DYNLRB1 and DYNLRB2, sharing 98% sequence similarity in mammals [13]. Mammalian DYNLRB1 has been studied mainly as an adaptor linking specific modules to the dynein complex, including SMAD2 complexes activated by TGFβ receptors [11,[14][15][16][17][18] and Rab6 or N-acetyl-Dglucosamine kinase (NAGK) for interactions with the Golgi compartment [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…2, 3), we analysed the presence of putative PKA phosphorylation sites in DynLRB1 that could regulate its function in this process. We found Serine-13 (S13) and S73 as good candidates, but S13 showed a low phosphorylation score (0.5) and was in fact discarded recently as a PKA target 32 . Instead, a large phospho-proteomic analysis identified S73 33 , which seems to be effectively phosphorylated by PKA 32 .…”
Section: Resultsmentioning
confidence: 90%
“…Along these lines, we have shown that PKA can directly phosphorylate km23-1 on specific serine residues, which is required for TGFβ effects on downstream signaling of cAMP-responsive element (CRE)-dependent events (ie, FN) and Smad/activin-responsive element (ARE) activity [37]. Thus, km23-1 effects on Ezrin, as well as on other AKAP scaffolds, may involve PKA activity.…”
Section: Discussionmentioning
confidence: 95%
“…For example, km23-1 is required for TGFβ1 production through dynein-independent Ras/ERK/Jun N-terminal kinase (JNK) pathways in TGFβ-sensitive epithelial cells [35]. This multifunctional regulator also plays a critical dynein-dependent role in Smad2 signaling in early endosomes [34], and it is regulated by protein kinase A (PKA) activation [37]. Depletion of km23-1 not only reduces fibronectin (FN) expression, but also RhoA activity [30], further demonstrating the critical nature of km23-1's regulatory functions.…”
Section: Introductionmentioning
confidence: 99%